What About Relationships between Green Innovation and Sustainable Development? A Bibliometric Analysis Review - Bianca Tiffani S; Melinda Malau (Journal of Business Social and Technology, 2023)
This research analyzed the relationship between green innovation and sustainable development. The method used in this research is bibliometric. The bibliometric analysis conveys the journal's authors, provides past, present, and future capabilities of this particular theme, and serves as a goal and guide for current researchers to understand the themes of green innovation and sustainable development. The research aims to empirically capture the intellectual form, capacity, and direction of knowledge development. Achieve the goal using the VOSViewer software and the Web of Science (WoS) scientific database. VOSviewer software was adopted as a bibliometric analysis tool to visualize author, country, journal and keyword networks. The analysis conducted on 4 November 2022 cites 2043 documents from 2015 to 2022. The results prove that the number of green and sustainable innovation publications has grown relevantly in the last eight years. Ranked first in China as the most productive country in green innovation and sustainable development research and ranked second in the USA with the involvement of lead authors and research institutes. Keyword analysis shows that studies on green innovation and sustainable development in the last eight years have focused on environmental, economic, and technological themes. The bibliometric analysis provides data relevant to the main themes studied regarding green innovation and sustainable development.